Beliefs and perceptions of genetic testing by clinical, demographic, and health characteristics: A U.S.-based study utilizing the health information national trends (HINTS) survey - Pranali G. Patel; Marvin E. Langston; Justin X. Moore; Yunan Han; Marquita W. Lewis-Thames; Lindsay Fuzzell; Saira Khan (Preventive Medicine Reports)
Objective: Genetic testing and precision medicine enhance early detection and personalized treatment, potentially reducing morbidity and mortality. We examined how beliefs and perceptions of genetic testing and precision medicine differ by cancer history, gender, rural-urban status, physical activity, and obesity. Methods: We analyzed 3865 respondents from the Health Information National Trends Survey (HINTS) 5, Cycle 4, administered February 2020–June 2020. We assessed the associations between cancer history, demographic and health-related factors, with knowledge, beliefs, and perceptions of genetic testing and precision medicine. Adjusted Odds Ratios (AORs) and 95 % Confidence Intervals (CIs) were calculated. Results: Cancer survivors were more likely to have had genetic testing (AOR = 1.61; 95 % CI, 1.03–2.53) and to want to know if a genetic change increases cancer risk (AOR = 1.65; 95 % CI, 1.12–2.44). Men were more likely to report knowledge of precision medicine (AOR = 1.52; 95 % CI, 1.16–1.98) but less likely to believe genetic information is important for cancer prevention (AOR = 0.72; 95 % CI, 0.55–0.94). Those with less physical activity were less likely to report knowledge of precision medicine (AOR = 0.67; 95 % CI, 0.47–0.96) and genetic tests (AOR = 0.70; 95 % CI, 0.51–0.97). Individuals with obesity were more likely to believe genetic information is important for preventing (AOR = 1.36; 95 % CI, 1.06–1.75) and treating cancer (AOR = 1.27; 95 % CI, 1.02–1.59). Conclusion: Knowledge and beliefs about genetic testing and precision medicine vary by sociodemographic factors, in particular individuals with obesity are more likely to value genetic information.